IMPLEMENTASI DAN EVALUASI WEB SCRAPING PADA DATA JURNAL SINTA - Indra Nasution; Muhammad Iqbal (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The development of digital technology has increased the need for access to scientific information, especially related to academic journal publications. The Science and Technology Index (SINTA) website is one of the main platforms that provides information on accredited scientific journals in Indonesia. However, the process of searching and collecting journal data on the website is still done manually, so it is less efficient when the amount of data needed is large enough. This research aims to implement and evaluate web scraping techniques in collecting journal data on the SINTA website so that the data acquisition process can be carried out automatically, quickly, and in a structured manner. The research method uses an implementive approach through the stages of literature study, analysis of the structure of website pages, development of a system using the Python programming language with the BeautifulSoup library, data collection, database storage, and evaluation of extraction results. The results of the study show that the implementation of the web scraping technique  succeeded in obtaining as many as 15,456 journal data from the SINTA website in 2026 which includes information on journal names, publishing institutions, accreditation categories, ISSN, fields of science, and journal website links. The developed system is also capable of storing data in a structured manner into a database and supports regular information updates. The results of the evaluation show that the web scraping technique is able to improve the efficiency of data collection, minimize manual processes, and produce more systematic journal data. Thus, the implementation of web scraping techniques can be an effective solution in supporting the needs of academics and researchers to obtain journal information quickly and accurately. Keywords: Web Scraping, SINTA, Scientific Journals, Python, Beautifulsoup, Data Extraction.   Abstrak: Perkembangan teknologi digital telah meningkatkan kebutuhan akses terhadap informasi ilmiah, terutama yang berkaitan dengan publikasi jurnal akademik. Situs web Indeks Sains dan Teknologi (SINTA) merupakan salah satu platform utama yang menyediakan informasi tentang jurnal ilmiah terakreditasi di Indonesia. Namun, proses pencarian dan pengumpulan data jurnal di situs web tersebut masih dilakukan secara manual, sehingga kurang efisien ketika jumlah data yang dibutuhkan cukup besar. Penelitian ini bertujuan untuk mengimplementasikan dan mengevaluasi teknik web scraping dalam pengumpulan data jurnal di situs web SINTA sehingga proses akuisisi data dapat dilakukan secara otomatis, cepat, dan terstruktur. Metode penelitian menggunakan pendekatan implementasi melalui tahapan studi pustaka, analisis struktur halaman web, pengembangan sistem menggunakan bahasa pemrograman Python dengan pustaka BeautifulSoup, pengumpulan data, penyimpanan basis data, dan evaluasi hasil ekstraksi. Hasil penelitian menunjukkan bahwa implementasi teknik web scraping berhasil memperoleh sebanyak 15.456 data jurnal dari situs web SINTA pada tahun 2026 yang mencakup informasi tentang nama jurnal, lembaga penerbitan, kategori akreditasi, ISSN, bidang ilmu, dan tautan situs web jurnal. Sistem yang dikembangkan juga mampu menyimpan data secara terstruktur ke dalam basis data dan mendukung pembaruan informasi secara berkala. Hasil evaluasi menunjukkan bahwa teknik web scraping mampu meningkatkan efisiensi pengumpulan data, meminimalkan proses manual, dan menghasilkan data jurnal yang lebih sistematis. Dengan demikian, implementasi teknik web scraping dapat menjadi solusi efektif dalam mendukung kebutuhan akademisi dan peneliti untuk memperoleh informasi jurnal dengan cepat dan akurat. Kata kunci: Web Scraping, SINTA, Jurnal Ilmiah, Python, Beautifulsoup, Ekstraksi Data.